The Oxford dictionary of architecture / James Stevens Curl ; Susan Wilson - Curl, James Stevens
Written in a clear and concise style, this illustrated dictionary covers every period of Western architectural history. The text is complemented by over 250 line drawings, labelled cross-sections, and diagrams. There are more than 900 new entries, including hundreds of new biographical entries on leading historical architects, as well as subjects such as algorithmic design, digital architecture, and parametric design, and many entries expanding the coverage of landscape architecture.